Factors influencing injury or death due to traumatic events in Afghanistan's crisis-affected populations: a cross-sectional nationwide study. Issue 12 (5th December 2022) - Noh, Jin-Won; Lee, Lena J; Kim, Kyoung-Beom; Cha, Jiho; Kwon, Young Dae
Abstract : Objective: Afghanistan, with one of the world's largest refugee populations, suffers an enormous burden of injury resulting in loss of life. This study aims to identify the epidemiology of injuries or death in the crisis-affected populations across Afghanistan and to investigate factors associated with injuries or deaths due to traumatic events. Design: Cross-sectional study. Setting: This study analysed Whole Afghanistan Assessment 2019 data. This survey geographically covered all 34 accessible provinces in Afghanistan. Participants: 31 343 displaced and shock-affected households in Afghanistan. Primary and secondary outcome measures: Injury or death of household members due to traumatic events. Results: 2561 (8.2%) reported at least one household member had been injured or deceased because of a significant conflict or natural disaster in the past year. Households experienced significant events such as active conflict or violence (prevalence ratio, PR=5.575, p<0.001), earthquake (PR=3.118, p=0.004), flood (PR=1.534, p=0.008) and avalanche or heavy snowfall (PR=3.450, p<0.001) were significantly associated with injury or death. The likelihood of injury or death was significantly higher for long-distance households than for households living within a 5 km radius of the nearest healthcare facilities (6–10 km: PR=1.402, p=0.030; >10 km: PR=1.560, p=0.020). Conclusion: The study provides an epidemiological profile of injuries or death in crisis-affected populations across Afghanistan. Results also suggest that certain factors place the crisis-affected populations in Afghanistan at high risk for injuries or death, which can inform the development of surveillance and prevention programmes, the monitoring of patterns over time and the formulation of healthcare policies.